World of mental disease: perceptions and perspective of the health disease process - Gabriela Zenatti Ely; Marlene Gomes Terra; Adão Ademir da Silva; Fernanda Franceschi de Freitas; Cristina Thum; Éder Luís Arboit (Universidade Federal de Santa Maria, 2018)
Aim: to unveil the perception of the human being in the discovery of the world of mental illness and the prospects in the health disease process. Method: phenomenological study developed with 10 adults undergoing treatment in a psychiatric inpatient unit of a public hospital in a municipality in the south of Brazil. The production of data occurred through the phenomenological interview from January to March, 2014. Paul-Ricoeur's phenomenology-hermeneutics and Maurice Merleau-Ponty's theoretical-philosophical reference were used to understand the discourses. Results: the diagnosis of mental illness permeates the experience by generality and habit, which expose the historical paradigms. However, when it is shown as a body itself, the singularity emerges as a being in the world for the perceptions of the disease health process. Conclusion: to do so, it is necessary to unveil the real needs of the human being, in order to weave networks of meanings before the health disease and therapeutic perspectives processes.